Pemikiran Syahrur Vis A Vis Muhyar Fanani dan Salim al-Jabi pada Penggunaan Hijab dalam Konteks “Lita’arafu” - Baihaqi, Baihaqi; Ahmad Musadad; Tri Pujiati (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Muhammad Syahrur's thoughts on Islamic law, particularly regarding the hijab, offer a different approach compared to classical understandings. In the concept of lita’arafu (mutual recognition), Syahrur argues that wearing the hijab in public spaces should not hinder social interaction. This view is criticized by Muhyar Fanani and Salim al-Jabi, who believe that Syahrur's approach to Islamic law is overly rationalistic and lacks consideration of normative aspects in religious texts. This study comparatively examines Syahrur’s perspective with the critiques of Muhyar Fanani and Salim al-Jabi concerning the use of the hijab in public spaces. Through qualitative analysis of primary texts, this study finds that Syahrur emphasizes the minimal and maximal limits in Islamic law, while Fanani and al-Jabi tend to adopt a textual and contextual approach to understanding the hijab. This study asserts that Islamic legal thought must remain open to new interpretations without disregarding shar’i principles. The findings of this research are expected to provide new perspectives in contemporary Islamic legal discourse, particularly regarding the use of the hijab in social life.